Robotic Platforms for Therapeutic Flexible Endoscopy: A Literature Review - Naoya Tada; Kazuki Sumiyama (Diagnostics, 2024)
Flexible endoscopy, initially developed for diagnosis and tissue sampling, has been adapted for therapeutic interventions, leading to the emergence of natural orifice transluminal endoscopic surgery (NOTES) in the 2000s. The need for a triangulation function to enhance the intuitiveness and safety of NOTES has prompted the development of dual-arm, flexible endoscopic robotic platforms. Although the global interest in NOTES has decreased in the last decade, no-scar surgery concepts are still being applied to other complex endoluminal interventions, such as endoscopic submucosal dissection (ESD) and endoscopic full-thickness resection (EFTR), with ongoing research and development. The application of robotics in flexible endoscopy may facilitate the standardization of these procedures and expedite their global spread. Various robotic platforms have been developed and tested in the preclinical and clinical settings to demonstrate their efficacy and safety. In this article, we review the publications on technology and elucidate their advantages and existing challenges.